Problems of employment and adaptation of repatriates and their influence on the internal labor migration in Kazakhstan - Zhapakov, Sabyrzhan M.; Omirzhanov, Yesbol T.; Maulen, Aidana; Omirtay, Roza; Azhinurina, Dinara A. (Human systems management, 2020)
BACKGROUND: This article provides a full description of the state policy of the Republic of Kazakhstan on employment and adaptation of repatriates (oralmans) and identify problematic issues in this field. We paid attention to the main problems of repatriates in the homeland and analyzed the influence of oralmans on the internal labor migration in Kazakhstan. OBJECTIVE: This is the first independent study that investigates the Kazakh people who have returned from abroad, who form part of the population of internal labor migration. METHODS: Various study methods were used, including analysis and synthesis, comparison and observation. RESULTS: The authors analyzed historical aspects of the formation Kazakh diaspora and irredenta abroad, as well as provide information about the return of oralmans to the homeland. Furthermore, we separately examined the problems that oralmans face after returning to their homeland, and tried to identify the cause of each problem. The main problem was unemployment among oralmans. Because of the lack of a permanent job, oralmans often become subjects of internal labor migration. CONCLUSIONS: We analyzed various statistical data in terms of the numbers, formations, and dispositions of the oralmans. We furthermore analyzed the measures implemented by the state to solve existing problems. In the concluding part of the article, the authors give concrete recommendations on how to prevent the participation of oralmans in internal labor migration.